In Vivo Anti-Inflammatory Activity of Durio zibethinus Murray Leaf Ethanol Extract in Male Wistar Rats - Muliana, Hilda (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Inflammation is a physiological response that can become a serious health problem if excessive. This study aims to evaluate the anti-inflammatory effectiveness of durian leaf ethanol extract (Durio zibethinus Murray) on male white rats. The study used a post-test only control group design with male Wistar rats aged 2–3 months, weighing 180–210 g. The test animals were divided into five groups: negative control (CMC Na), positive control (diclofenac sodium), and three treatment groups with doses of 200, 400, and 800 mg/kg BW of durian leaf ethanol extract. Inflammation was induced by egg white injection into the sole of the foot. Edema volume was measured using a mercury plethysmometer. Data analysis used one-way ANOVA and Tukey's post-hoc test. The results showed that the extract contains flavonoids, saponins, and steroids. A dose of 400 mg/kg BW provided the second highest edema inhibition (34.34% at 120 minutes) after the standard drug sodium diclofenac (37.83% at 360 minutes), and the results of the ANOVA test showed a p-value <0.05 there was a significant difference compared to the negative control. Ethanol extract of durian leaves has anti-inflammatory potential, although its effectiveness has not yet matched standard drugs, so it has the potential to be developed as a safer natural-based therapy.